O fazer-se professor de escolas básicas: propostas metodológicas e experiências na formação de professores por meio do PIBID de história da UEPB Guarabira-PB (2012-2016) - Nunes, Sandeilson Beserra (2020)
This dissertation is an investigative work about the making of a teacher in basic education in the city of Guarabira, Paraíba (2012-2016) having as analysis object the Institutional Teaching Initiation Scholarship Program - PIBID (Programa Institucional de Bolsas de Iniciação à Docência [PIBID]) of the State University of Paraíba - UEPB (Universidade Estadual da Paraíba [UEPB]). The experiences of teachers and scholarship holders that were part of the implementations and realizations of the Program were problematized, emphasizing the historical knowledge and history teaching. PIBID and its writings have been associated to new and old educational practices, and in other times have collaborated to amplify debates on teacher training, moving a discourse in favor of which kind of professional the degree courses in History intend to form, which habits and practices were sought embody in these subjects who have undergone training within PIBID. The program has appeared in recent years as references to debates about History Teaching and teacher training; this was seen on various symposia and events throughout Brazil that brought it to the center of the debate and the works by it developed. The research dialogued with official documents created by the public powers that regulated actions and objectives in a way to make possible their implementation in basic education schools, having the Universities as partners. When looking at official documents it was observed an object of plural study made by several subjects. These documents presented information on the creation history of PIBID and how the documents started to guide its actions, also the expansion of its capability, including more undergraduate courses and Universities. In the whole of its vast production of didactic materials and in-class activities, we highlight this space presenting works developed by the participants of PIBID that were involved with their teaching training through exchanges of experiences that implied in their teaching re-making. The research also dialogued with the epistemological line of History Teaching and with approaches to teacher training and their profession, experiences, Oral History and memory, encompassing the becoming teacher and the plural relationships that permeate it. From these paths the analysis of the official documents were important to understand how these discourses echoed in school and in the activities of PIBID. The main sources that make up the documentary corpus of the research are interviews, articles, reports, photographs, didactic materials and films that composed the day by day of PIBID at the schools; these documents made possible the construction of this dissertation. The analysis of speeches about the work and the teacher training started from what was proposed, (TARDIF; LESSARD, 2013) and (TARDIF, 2014) are utilized as methodology, making possible to problematize experiences of the teachers and how are they acquired and socialized throughout their teacher training process. When discussing experiences the speeches were elaborated seeking to understand how they interfered in the construction of the methodological proposals that were developed among the participants of PIBID. For this purpose were made use of concepts as of (THOMPSON,1980), (PAIM, 2005) and in parallel with the concepts of History Teaching (BITTENCOURT 2009) permeating this discourse, contributing to historicize the becoming teacher in basic education and methodologies for teacher education in History.